Dampak KDRT terhadap Perkembangan Mental Seorang Anak dalam Film Bolehkah Sekali Saja Kumenangis - Ahmad Abi Nugroho; Robet Yona Emagene Ikhwan Ma'rufi; Muhammad Khorudin; Ahmad Muhammad Mustain Nasoha (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
Bolehkah Sekali Saja Kumenangis is an emotional drama that will air starting October 17, 2024. Directed by Reka Wijaya Kusuma. The film "Bolehkah Sekali Saja Kumenangis" is a drama that tells the life of a woman named Tari, played by Prilly Latuconsina, who has trauma from her father who often commits domestic violence. This study aims to describe the impact of domestic violence on the mental development of a child in the film Bolehkah Sekali Saja Kumenangis. This research is a qualitative descriptive study. The data source for this study is the film Bolehkah Sekali Saja Kumenangis. The data in this study are words and sentences related to domestic violence and mental health contained in the film Bolehkah Sekali Saja Kumenangis. Data collection was carried out by listening to and recording words/sentences related to domestic violence and mental health in the film Bolehkah Sekali Saja Kumenangis. Based on the results of the data analysis, the conclusion is that a child who has experienced domestic violence will experience several impacts such as physical injury, trauma, and impaired mental health.